2013
DOI: 10.1007/s10637-013-9987-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationship (SAR) of withanolides to inhibit Hsp90 for its activity in pancreatic cancer cells

Abstract: Withaferin A (WA), a naturally occurring steroidal lactone, directly binds to Hsp90 and leads to the degradation of Hsp90 client protein. The purpose of this study is to investigate the structure activity relationship (SAR) of withanolides for their inhibition of Hsp90 and anti-proliferative activities in pancreatic cancer cells. In pancreatic cancer Panc-1 cells, withaferin A (WA) and its four analogues withanolide E (WE), 4-hydroxywithanolide E (HWE), 3-aziridinylwithaferin A (AzWA) inhibited cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 38 publications
1
53
1
Order By: Relevance
“…However, we have not observed development of resistance in vitro after sustained treatment with DBZ plus withaferin A in any of our models, suggesting that T-ALL cells need to overcome significant barriers to develop resistance to this combination. Mechanisms proposed for the antitumor effects of withaferin A include proteasome (24), HSP90 (25), NFKB (26) inhibition, and induction of reactive oxygen species (ROS) (27). However, these mechanisms seem to be cell-type specific, as functional assays revealed decreased ROS levels and no or minimal impact of withaferin A in HSP90, proteasome, or NFKB activity in T-ALL cells (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have not observed development of resistance in vitro after sustained treatment with DBZ plus withaferin A in any of our models, suggesting that T-ALL cells need to overcome significant barriers to develop resistance to this combination. Mechanisms proposed for the antitumor effects of withaferin A include proteasome (24), HSP90 (25), NFKB (26) inhibition, and induction of reactive oxygen species (ROS) (27). However, these mechanisms seem to be cell-type specific, as functional assays revealed decreased ROS levels and no or minimal impact of withaferin A in HSP90, proteasome, or NFKB activity in T-ALL cells (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The broad peak at 3600-3200 cm -1 may be due to the O-H functional group frequency of the hydroxyl groups present in phytoconstituents present in the ashwagandha root extract. The presence of epoxide, unsaturated lactone, 1-keto-2-ene functions plays a vital role to elicit the pharmacological activities of withanolides [14,[55][56][57]. In summary, FT-IR results suggest that there was a little impact of Consciousness Energy Healing Treatment on W. somnifera at the atomic level to reduce the force constant of O-H (str.)…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopymentioning
confidence: 93%
“…The vibrational frequencies for C=O, C-O, and C-C groups in the Biofield Energy Treated sample was observed with respect to the control sample. The presence of epoxide, unsaturated lactone, 1-keto-2-ene functions play a vital role to elicit the pharmacological activities of Thermal and Behavioral Properties of Ashwagandha (Withania somnifera) Root Extract withanolides [14,[55][56][57]. This results revealed that the force constant for the functional groups present in the phytoconstituents was altered compared with the control sample.…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopymentioning
confidence: 94%